Effect Of Coffee Drinking Habit to Blood Pressure and Hemoglobin Levels on Women of Childbearing Age - Minarni Wartiningsih; Tatas Hardo Panintingjati Brotosudarmo; Vincent Aurelius Gonaldy; Ni Njoman Juliasih; Hanna Silitonga; May Fanny Tanzilia (Masters Program in Public Health, 2024)
Background: Tenggerese people, especially women, have a habit of drinking coffee, and it has become a daily habit. Coffee is often associated with risk factors for diseases in the community such as anemia and hypertension. This study aims to determine the effect of coffee drinking quantity (1-2 cups, 3-4 cups, and ≥ 5 cups of coffee per day) on hemoglobin levels and blood pressure. Subjects and Method: A quantitative study with a cross-sectional study design was done. This study population was women of reproductive age (15 to 49 years) in Ngadipuro Hamlet, Tengger, East Java, Indonesia. The independent variable of this study is the of daily coffee drinking per cup and the dependent variable of this study is the hemoglobin levels in women of childbearing age. The study instrument used was a questionnaire to screen for those who were a daily coffee drinker and a blood hemoglobin rapid test kit was used to measure the level of hemoglobin.The number of samples in this study was 193 respondents which was chosen using the random sampling technique. Analysis of the quantity of coffee drinking on hemoglobin levels by the Annova test while on blood pressure by the Kruskal Wallis test through SPSS software. Results: The result showed that the quantity of coffee per day on hemoglobin levels had a significance p<0.001. While the quantity of coffee per day on blood pressure had a significance p=0.361. Conclusion: It can be concluded that drinking 1-2 cups of coffee, 3-4 cups, and ≥ 5 cups of coffee daily simultaneously affects hemoglobin levels. In this case, the more quantity of coffee per day, the lower the hemoglobin level. However, the quantity of coffee had no significant effect on blood pressure.